Effect of growing seasons, plant extracts with various rates on Black Bean Aphid, Aphis Fabae (Aphididae: Homoptera) - qadir, rebin abdalrahman; M. Amin, Havall; J. Majeed, Ardalan (Kurdistan Journal of Applied Research, 2018)
Four plant extracts: Eucalyptus (Eucalyptus sp), Onion (Allium cepa Linn), Garlic (Allium sativum) and Cinnamon (Cinnamomum sp) with three extraction rates (0, 1 and 3) % in 2016 and 2017 seasons were used against aphid population in broad bean (Vicia faba). Some plants characteristic; Plant Height (cm), Fresh Weight.Plant-1 (g), Dry Weight.Plant-1 (g), Number of Pods.Plant-1, and aphid’s dead number after 6 hours and 24 hours were taken. Eucalyptus affected significantly on Number of Pods.Plant-1compared with the other extraction (7.416). As the extraction rate increased, all parameters increased. Pearson’s correlation test for traits in 2017 season indicated that there were a significant strong correlate and better than 2016 season among Number of Pods .Plant-1, Fresh Weight.Plant-1 (r = 0.770**), Dry Weight .Plant-1 (r = 0.816**), and M24 (r = 871**). Based on Number of Pods.Plant-1, the best interaction between the season, extraction types, and extraction rates, was a combination of the 2017 season × Eucalyptus extraction × 1% Extraction rate.